P-Hydroxyacetophenone Ameliorates Alcohol-Induced Steatosis and Oxidative Stress via the NF-κB Signaling Pathway in Zebrafish and Hepatocytes - Huang, Sha; Zhou, Chuying; Zeng, Ting; Li, Yujia; Lai, Yuqi; Mo, Chan; Chen, Yuyao; Huang, Shaohui; Lv, Zhiping; Gao, Lei (Frontiers in Pharmacology, 2020)
Alcoholic liver disease (ALD), recognized as an important health problem worldwide, is a direct consequence of alcohol consumption, which can induce alcoholic fatty liver, alcoholic steatohepatitis, fibrosis and cirrhosis. p-Hydroxyacetophenone (p-HAP) is mainly used as a hepatoprotective and choleretic compound and has anti-hepatitis B, antioxidation and anti-inflammatory effects. However, no experimental report has focused on p-HAP in ALD, and the effect and mechanism of p-HAP in ALD remains a mystery. In addition, there is no research on p-HAP in the treatment of ALD. The potential molecular mechanisms of p-HAP against acute alcoholic liver injury remain unknown. In this study, we aimed to investigate whether p-HAP alleviates ALD and to elucidate the underlying molecular mechanisms. At 4 days postfertilization (dpf), zebrafish larvae were exposed to 350 mmol/L ethanol for 32 h and then treated with p-HAP for 48 h. We chose different endpoints, such as morphological changes in liver shape and size, histological changes, oxidative stress-related free radical levels, apoptosis and NF-κB expression, to verify the essential impact of p-HAP in alcohol-induced liver lesions. Subsequent experiments, including Oil Red O, Nile Red, and pathological hematoxylin and eosin (H&E) staining, immunochemistry, Western blot analysis and TUNEL staining, revealed that p-HAP treatment reduced alcoholic hepatic steatosis in a dose-dependent manner. Specifically, the 50 μM dose resulted in an almost normal response. This finding suggested that p-HAP might inhibit alcoholic-induced liver steatosis and injury by attenuating lipid accumulation and reducing oxidative stress and apoptosis via the NF-κB signaling pathway.